2019
DOI: 10.1080/10494820.2019.1674888
|View full text |Cite
|
Sign up to set email alerts
|

Investigating teachers’ adoption of MOOCs: the perspective of UTAUT2

Abstract: The number of the massive open online courses (MOOCs) around the globe is on the rise. Despite the popularity of MOOCs, they have received less attention from faculty members around the globe compared to other less-traditional and digital education models. MOOCs can be challenging for teachers to use. As such, understanding how to facilitate teachers' adoption of MOOCs is very important to better promote their use. The aim of this research paper is to investigate the drivers of teachers' acceptance and use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
122
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(144 citation statements)
references
References 63 publications
14
122
7
1
Order By: Relevance
“…Among these, UTAUT2(Unified theory of acceptance and use of technology) by Venkatesh et al, (2012) has been applied widely in various domains to understand users' behavior concerning different technologies. But the model is yet to be validated within the online teaching platform for various reasons (Tseng et al, 2019). As UTAUT2 considers the perspective of voluntary users (i.e., consumers), it matches well with online teaching.…”
Section: Framework Of Technology Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, UTAUT2(Unified theory of acceptance and use of technology) by Venkatesh et al, (2012) has been applied widely in various domains to understand users' behavior concerning different technologies. But the model is yet to be validated within the online teaching platform for various reasons (Tseng et al, 2019). As UTAUT2 considers the perspective of voluntary users (i.e., consumers), it matches well with online teaching.…”
Section: Framework Of Technology Adoptionmentioning
confidence: 99%
“…Previous research studies on technology adoption (Davis, 1989;Venkatesh et al, 2012), meta-analyses (Dwivedi et al, 2019;Williams et al, 2015), and empirical studies on online learning (Chiu and Wang, 2008;El-Masri and Tarhini, 2017;Mosunmola et al, 2018;Pynoo et al, 2011), indicated the significant and vital impact of performance expectancy on behavioral intention. Previous research studies have emphasized the significant impact of PE on the intention to adopt web-based learning tools (Tseng et al,2019;El-Masri and Tarhini, 2017;Tarhini et al, 2016;Pynoo et al, 2011).In this study, PE has been validated to comprehend the perception of academicians about online teaching during the COVID -19 outbreak. In this study, it is projected that if university teachers consider that online teaching is beneficial and may add to their teaching experience, then they are more likely to indulge themselves with the system.…”
Section: Framework Of Technology Adoptionmentioning
confidence: 99%
“…Some studies highlighted Facilitating Conditions as factors that affect the use of technology (Tseng et al, 2019;Mei et al, 2018;Wong, 2016;Sangeeta & Tandon, 2020;Huang, Teo & Zhou, 2017;Teo et al, 2019;Prasojo et al, 2020, Wong, 2016Mtebe, Mbwilo & Kissaka, 2016;McCulloch et al, 2018). Yew and Tan (2020) found out that the most important factor that affected teachers' intention to adopt online educational technologies was the accessibility of infrastructure and learning resources.…”
Section: Facilitating Conditionsmentioning
confidence: 99%
“…It also has theoretical value to explain migration behavior under emergency management. Second, previous studies explained students' online learning using behavior mainly applied theories such as Technology Acceptance Model (Huang and Teo, 2019 ; Ashrafi et al, 2020 ; Eksail and Afari, 2020 ), Expectation Confirmation Theory (Joo et al, 2018 ; Dai et al, 2020 ), and Extending The Unified Theory of Acceptance and Use of Technology (UTAUT2) (Tseng et al, 2019 ). However, different from the PPM theory, previous theories need to require fixed research frameworks and variables.…”
Section: Introductionmentioning
confidence: 99%